2014
DOI: 10.1517/14740338.2014.908182
|View full text |Cite
|
Sign up to set email alerts
|

Serotonergic antidepressants and perioperative bleeding risk: a systematic review

Abstract: SAds are associated with increased perioperative bleeding events, particularly abnormal bleeding and blood transfusions. From a clinical perspective, the potential bleeding risks of SAds in surgical settings need to be carefully weighed against their psychiatric benefits. Future research will need to investigate potential strategies to mitigate SAd-related bleeding risk in the surgical context.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0
4

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 35 publications
2
8
0
4
Order By: Relevance
“…458 Although analysis of two pharmacovigilance databases suggested that SSRIs were not associated with an increased risk of bleeding, 459 a recent systematic review including 13 relevant studies across a variety of surgical procedures showed that SADs were associated with increased risk of perioperative bleeding (odds ratio ¼ 1.21 1.21 to 4.14) and blood transfusions (odds ratio ¼ 0.93 to 3.71). 460 Clinicians should be aware of this increased bleeding risk with SAD use and carefully weigh it against the psychiatric benefits in all patients undergoing surgery. Discontinuation of SADs should be planned 2 weeks before the operation in patients with a high risk of bleeding and who are in a stable phase of depression.…”
Section: Recommendationmentioning
confidence: 99%
“…458 Although analysis of two pharmacovigilance databases suggested that SSRIs were not associated with an increased risk of bleeding, 459 a recent systematic review including 13 relevant studies across a variety of surgical procedures showed that SADs were associated with increased risk of perioperative bleeding (odds ratio ¼ 1.21 1.21 to 4.14) and blood transfusions (odds ratio ¼ 0.93 to 3.71). 460 Clinicians should be aware of this increased bleeding risk with SAD use and carefully weigh it against the psychiatric benefits in all patients undergoing surgery. Discontinuation of SADs should be planned 2 weeks before the operation in patients with a high risk of bleeding and who are in a stable phase of depression.…”
Section: Recommendationmentioning
confidence: 99%
“…12 Os inibidores da recaptação da serotonina estão associados a aumento do risco de sangramento por efeito secundário na agregação plaquetária. 13 Os inibidores de monoamino oxidase (IMAO) apresentam várias interações com medicações anestésicas como tramadol e meperidina, aumentando a liberação de serotonina. O uso de drogas simpaticomiméticos indiretas associado aos IMAO pode liberar uma grande quantidade de noradrenalina e produzir uma crise hipertensiva.…”
Section: F Antidepressivosunclassified
“…При терапии СИОЗС отмечается повышенный риск геморрагических осложнений [9] и периоперационной кровопотери, превышающей обычную [10] и требующей проведения трансфузии эритроцитов [10][11][12][13]. Риски возникновения кровотечения особенно велики при использовании препаратов с высокой и средней активностью в отношении ингибирования серотонинового транспортера (5-НТТ) [14,15].…”
Section: анамнез уровень убедительности рекомендаций Iiа (уровень досunclassified
“…сока [135]. Установлено, что прием СИОЗС ассоциирован с повышением риска возникновения внутричерепных кровоизлияний [9,136,138]. Хотя достоверной разницы влияния на риск кровотечения между препаратами с различной активностью в отношении ингибирования серотонинового транспортера (5-НТТ) не установлено, при высоком риске внутричерепного кровоизлияния/кровотечения рекомендуют предпочесть препараты с менее высокой активностью [138].…”
Section: профилактика геморрагических осложнений рекомендацияunclassified